32 SIMULATION-BASED EDUCATION FOR ACUTE STROKE. (18th November 2021) - Crowley, P; Saramago, I; Cannon, R; McGrath, K
Abstract: Background: Acute stroke requires efficient multi-disciplinary collaboration to deliver time-sensitive treatment in a prompt and effective manner. The European Stroke Organization (ESO) recommends simulation-based education (SBE) for stroke care. Studies have shown SBE improves door-to-needle times, which predict better patient outcomes. SimStars was a competition, run by the National Doctors Training and Planning leads for the South-SouthWest Hospitals Group, to develop in-situ SBE scenarios. We developed a SBE program for acute stroke in an Irish teaching hospital. Methods: Medical doctors and nursing staff are included in the SBE scenario as candidates/target learners. Patients are played by role-players. Anonymised data and neuroimaging from real patients is utilized to maximize fidelity to real life. Other participants, such as paramedics, can be included to facilitate scenarios as required. Candidates are briefed before each scenario. Clear learning objectives are set. All participants are provided with a script outlining their roles. Candidates are appraised using standard evaluation forms. A de-brief is undertaken to reinforce learning objectives. Results: We qualified for the final of SimStars by establishing a SBE program for acute stroke, including a video of a simulated scenario that can be utilized for demonstration purposes. 100% of candidates who have participated in the SBE program so far have stated that it made a valuable contribution to their learning in the field of stroke care. Conclusion: Stroke has been described as an exemplar of how SBE may benefit training along an entire clinical pathway. Scenarios can be adapted to cover an endless variety of stroke-related situations. SBE has been shown to improve hyper-acute clinical pathway performance and outcomes.